Characteristics of Materials Used by English-Speaking Linguists in their Publications: A Citation Study of Literature Requirements , Citing Functions, and Citing Trends - Yang, Sharon (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The study described in this paper used citation analysis as a research method to examine the significant characteristics of the literature cited by linguists and the changes in their patterns of bibliographic citations from 1969 to 1989. A total of 17,657 citations were analyzed. The investigated variables included form, time span, language distribution, subject dispersion. . .